2001
DOI: 10.1021/jp011384y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding in Concentrated Aqueous Solutions of 1,2-Dimethoxyethane:  Formation of Water Clusters

Abstract: The hydrogen bonding in concentrated aqueous solutions of 1,2-dimethoxyethane was studied by Raman spectroscopy of the O-H stretching band of water at various concentrations in the temperature range 218-315 K. The isotropic Raman spectra were analyzed by band decomposition, and two major components were identified in the spectra. They were assigned to the O-H stretching vibrations of water monomers and water molecules participating in clusters, respectively. The following picture of the hydration structure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…10). As temperature increases, water structuring around the nonpolar parts of solute molecules decreases 20. This means that the entropy gain upon the loss of water structuring is less at higher temperatures than at lower temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…10). As temperature increases, water structuring around the nonpolar parts of solute molecules decreases 20. This means that the entropy gain upon the loss of water structuring is less at higher temperatures than at lower temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…This in turn points to the possibility of existence of patches (clusters) of bulk-like water between the hydrated ion clusters. Similarly to the results for water structure in concentrated POE solutions [47], we can assume that at very low mole ratios (high salt concen- …”
Section: Salt Hydration At High Concentrationmentioning
confidence: 88%
“…Moreover, the hydrophobic part of the molecule favours the arrangement of water (W) molecules around DME, further compacting than in the pure water. In this respect, Raman spectroscopy studies performed by Goutev, Matsuura et al [24][25][26] on water + DME mixtures have shown that, at low DME content, hydration structures are observed in which water clusters are coordinated by hydrogen bonds on the oxygen atoms of the ether groups and, simultaneously, the methyl groups act as Physics and Chemistry of Liquids 13 hydrophobic centres. This leads to an increase in local order of the hydration structure around each conformer type of DME molecules which are of course surrounded by an environment of water clusters.…”
Section: Discussionmentioning
confidence: 99%